Growth curve models in retrospective memory and prospective memory: the relationship between prediction and performance with task experience. Issue 5 (18th August 2018) - Ng, Amanda R. J.; Bucks, Romola S.; Loft, Shayne; Woods, Steven P.; Weinborn, Michael G.
ABSTRACT: Older adults commonly experience declines in episodic memory that affect their daily lives. The aim was to examine whether the acquired metacognitive awareness that comes with task experience, indexed by meta-retrospective memory (meta-RM)/meta-prospective memory (meta-PM), influences how older adults predict performance on later trials. Participants were 178 community-dwelling older adults. RM performance and predictions were measured using a multi-trial word-list learning task. Predictions and performance for PM were measured using a PM paradigm. Change in RM/PM performance and predictions over the trials/blocks were modelled using latent growth curve analyses. For RM, both predictions and performance increased with task experience. However, for PM, neither performance nor predictions changed with task experience. Hierarchical multiple regressions revealed that metacognitive awareness acquired during the RM and PM tasks influenced how older adults' modified their predictions of subsequent task performance. Findings are consistent with [Toglia and Kirk's (2000). Understanding awareness deficits following brain injury. NeuroRehabilitation, 15 (1), 57–70] hypothesis that individuals compare ongoing performance to expectations based on metacognitive knowledge, such that a discrepancy between actual and expected performance may influence emergent awareness.